PSYCHOLOGICAL COMPATIBILITY OF STUDENTS IN DYADIC AND GROUP SPACES - Kondratiev, Sergey; Kalita, Vitaly; Yulina, Galina; Baranova, Ekaterina; Reva, Tatyana (Revista Inclusiones, 2020)
The article discusses the psychological compatibility of school students as a condition for the effectiveness of pedagogical and student interaction and personal development. The characteristic is given to pedagogical and student interaction from the position of establishing psychological contact between students, a teacher and students in a dyadic and group space. Studies on the psychological compatibility of students have been analyzed, and therefore, the following are considered: mechanisms of psychological contact in the classroom; “educational collaboration”; the effectiveness of academic work; individual psychological characteristics of partners; compatibility criteria in the learning process. The theoretical model of psychological compatibility in student activity at the level of the educational task, at the level of role interaction, at the level of motives and personal values is offered. The factors of psychological compatibility of students are identified: typical and stylistic features of student activity, role interaction, creative activity. The results of an empirical study of the psychological compatibility of primary school students in a number of secondary schools in Moscow are presented. Identification of psychological compatibility of learners, learners and the teacher in the group and dyad space was determined using the "quantitative assessment of compatibility", developed on the basis of modification of the methodology of studying psychological compatibility by R. L. Krichevsky, I. B. Antonova. In this case, the compatibility of the students was determined on the basis of mutual choices and the total scores received by each student. Mutual choices made it possible to determine compatibility options. The study of the relationship of students to the teacher was carried out on the basis of questions of this methodology, which relate to their interaction in the classroom and communication after class. The study of the teacher’s attitude toward students was carried out on the basis of the method of a modified color test of the relationships of A. M. Etkind. Verbal and logical thinking of the first grade students was studied on the basis of the "Fourth odd" method. The study of "school motivation" was carried out using the methodology "Motivational readiness for school" by T.I. Yurefieva. In order to determine the contribution of each of the considered factors, represented individually by psychological characteristics in psychological compatibility, a correlation analysis was carried out. It was found that the most significant influence on the psychological compatibility of a school student with a group is exerted by: “teacher’s attitude toward students,” “student’s attitude toward teachers,” “motivation”, and “verbal-logical” thinking do not play a large role in the psychological compatibility of students. The analysis of the" dyad "compatibility of respondents allowed us to empirically identify five "compatible" groups in each of the studied classes.